RASIONALITAS TUNTUTAN PROVINSI KALIMANTAN TIMUR UNTUK OTONOMI KHUSUS - Heru Cahyono (Masyarakat Indonesia, 2013)
The demand for autonomy in East Kalimantan seems premature since it does not have a strong legal basis. The demand for autonomy was raised after the cancelation of Act No.33/2004 on Financial Balance between Central and Local Government. On the one hand, the demand for autonomy seems reasonably well-justified that even though Kalimantan Timur is a natural resource rich province, yet its people are still living under poverty. From environmental viewpoint, the demand also seems reasonable. With the right to manage natural resources independently, Kalimantan Timur will be able to control the extraction of its resources, so as not to cause damage to the environment. On the other hand, the demand contains fundamental weaknesses with regards to capacity for implementing a good governance and the readiness of local human resources. There are still doubts about the relative size of the budget that cannot be absorbed and the lack of transparency in the use of development funds in the province.Keywords: Local Autonomy, East Kalimantan, Rationality, Natural Resource